Ibu Kota Nusantara Sebagai Daerah Khusus Berdasarkan Desentralisasi Asimetris - Purwopangestu, Krisna Bagas; Wahyuningsih, Sri (UI Scholars Hub, 2026)
This research examines the legal issue concerning the administration of regional government in Nusantara Capital City (IKN) which has been consider by some scholars as demonstrating deviations from the principle of decentralization. This research takes a position contrary to the mainstream legal discourse that argues there is a conceptual deviation in the model of regional governance in IKN. This research is normative legal research employing a conceptual approach and statutory approach with data collected through library research. This research argues that the administration of regional government in IKN does not indicate any deviation from the principle of decentralization. IKN is a special region established based on asymmetric decentralization, whose governance arrangement is not subject to the general decentralization model as regulated in Law No. 23 of 2014 on Regional Government. Therefore, differences in the model of regional governance in IKN should be understood as a consequence of its status, rather than as a form of deviation in the decentralized system of regional government.